Clinicopathological feature and prognosis of primary hepatic gastrointestinal stromal tumor. (3rd August 2016) - Liu, Zhen; Tian, Yangzi; Liu, Shushang; Xu, Guanghui; Guo, Man; Lian, Xiao; Fan, Daiming; Zhang, Hongwei; Feng, Fan
Abstract: Compared to gastric gastrointestinal stromal tumor (GIST), hepatic GIST is very rare in clinic. Reports on clinicopathological feature and prognosis of this rare disease are limited in literature. The purpose of this study was, therefore, to summarize clinical and pathological features as well as prognosis of the primary hepatic GIST. One case of primary hepatic GIST from our center and 22 cases reported in MEDLINE or China National Knowledge Infrastructure (CNKI) were enrolled into this study. Clinicopathological features as well as survival data of hepatic GIST were analyzed and compared with 297 gastric GISTs and 59 small intestinal GISTs from our center. Majority of the 22 cases (95.7%) of hepatic GIST was larger than 5 cm in size, and 75.0% of the tumors were over 5/50 HPF in mitotic index. Most of the hepatic GISTs (85.7%) displayed spindle cell shape in morphology. All of the hepatic GIST (100%) enrolled in this study were classified as high‐risk category by the National Institute of Health (NIH) risk classification. The 5‐year median disease‐free survival (DFS) time was 24.0 months and 5‐year disease‐specific survival (DSS) rate was 33.3%, respectively. Distribution of clinicopathological features was significantly different among hepatic, gastric, and small intestinal GIST. The DFS and DSS of hepatic GIST were significantly lower than those of the other two groups. Majority of the hepatic GIST is large in size and highly malignant. Prognosis of the primary hepatic GIST is worse than that of gastric GIST and small intestinal GIST. Abstract : Clinicopathological features and prognosis of hepatic gastrointestinal stromal tumor (GIST)s are limited due to the extremely rare incidence. This study indicated that majority of the hepatic GIST is large in size and highly malignant. Prognosis of the primary hepatic GIST is worse than that of gastric and small intestinal GIST.